Odpowiedź :
Odpowiedź:
zad 1
Rozwiązanie w załącznikach
zad 2
a)
2(x - 1) = 6
2x - 2 = 6
2x = 6 + 2 = 8
x = 8/2 = 4
b)
3/4x + 1/4 = 1
3,4x = 1 - 1/4 = 3/4
x = 3/4 : 3/4 = 3/4 * 4/3 = 1
c)
4(x - 2) = 2x + 5
4x - 8 = 2x + 5
4x - 2x = 5 + 8
2x = 13
x = 13/2 = 6 1/2 = 6,5
d)
2x - x/2 + 1 = 5 | * 2
4x - x + 2 = 10
3x + 2 = 10
3x = 10 - 2 = 8
x = 8/3 = 2 2/3
zad 3
a)
a)
2x + 1/2 ≥ 3
2x ≥ 3 - 1/2
2x ≥ 2 1/2
x ≥ 2 1/2 : 2
x ≥ 5/2 * 1/2
x ≥ 5/4
x ≥ 1 1/4
b)
4(x - 3) + 7 ≤ 3(x + 5) - 13
4x - 12 + 7 ≤ 3x + 15 - 13
4x - 5 ≤ 3x + 2
4x - 3x ≤ 2 + 5
x ≤ 7
Ilustracja na osiach liczbowych w załączniku 3
zad 4
(x - 3)/2+ 5 > x + (x + 3)/5 | * 10
5(x - 2) + 50 > 10x + 2(x + 3)
5x - 10 + 50 > 10x + 2x + 6
5x + 40 > 12x + 6
5x - 12x > 6 - 40
- 7x > - 34
7x < 34
x < 34/7
x < 4 6/7